Manufactures Building and Machinery Building, taken from the porch of the Agriculture Building, Alaska Yukon Pacific Exposition, Seattle, 1908. - Nowell, Frank H., 1864-1950 (1908)
PH Coll 727.454 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number